2007
DOI: 10.1111/j.1468-1331.2006.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

The seizure outcome after amygdalohippocampectomy and temporal lobectomy

Abstract: The aim of this study was to compare the seizure outcome of two different types of epilepsy surgery, selective amygdalohippocampectomy (AHE) and anterior temporal lobectomy (ATLE) in patients with temporal lobe epilepsy. We included 114 patients who had mesio-temporal lobe epilepsy and hippocampal sclerosis or gliosis on histology. Patients had ATLE if the non-dominant hemisphere was affected or if the whole temporal lobe was atrophic. Patients had AHE if the dominant hemisphere was affected. Standardized seiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 25 publications
0
50
1
Order By: Relevance
“…On the other hand, some investigators have recorded neocortical epileptiform spikes with cortical electrodes, 1,35 indicating that tailored resection of the temporal neocortex is Selective amygdalohippocampectomy versus anterior temporal lobectomy in the management of mesial temporal lobe epilepsy: a meta-analysis of comparative studies essential for MTLE. Other studies have suggested that better seizure outcomes were achieved in patients who underwent ATL than in those who underwent SelAH, 3,21 and that no significant differences in neuropsychological outcomes were found between the surgical strategies. 12,42 A review attempted to pool studies comparing ATL and SelAH for MTLE to test the hypothesis that the latter procedure produces similar seizure and favorable neuropsychological outcomes, and the conclusion was concordant with the hypothesis.…”
Section: ©Aans 2013mentioning
confidence: 91%
“…On the other hand, some investigators have recorded neocortical epileptiform spikes with cortical electrodes, 1,35 indicating that tailored resection of the temporal neocortex is Selective amygdalohippocampectomy versus anterior temporal lobectomy in the management of mesial temporal lobe epilepsy: a meta-analysis of comparative studies essential for MTLE. Other studies have suggested that better seizure outcomes were achieved in patients who underwent ATL than in those who underwent SelAH, 3,21 and that no significant differences in neuropsychological outcomes were found between the surgical strategies. 12,42 A review attempted to pool studies comparing ATL and SelAH for MTLE to test the hypothesis that the latter procedure produces similar seizure and favorable neuropsychological outcomes, and the conclusion was concordant with the hypothesis.…”
Section: ©Aans 2013mentioning
confidence: 91%
“…It has been described by most major series that postoperative seizure control does not differ significantly between the two approaches 7,13,14,15,16,17,18,19,20,21 . Nonetheless, three studies have found better seizure-control in patients submitted to ATL 4,22,23 . Similarly, two recent systematic reviews concluded that ATL is associated with a reduced rate of seizure recurrence compared to SelAH 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, ATL and SelAH groups usually have unequal number of patients. Also an issue, follow-up periods are frequently of just a couple of years 4,18 . Finally, most studies include individuals with TLE due to several different pathologies, such as tumors, malformations of cortical development, MTS, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We prefer to use "corticoamygdalohippocampectomy", which describes the technique more accurately. However, studies comparing SAH and CAH by Ozkara et al (12,(14)(15)(16). There is also still no consensus on the extent of resection.…”
Section: Discussionmentioning
confidence: 99%